THE MEANING OF VERBAL AND NONVERBAL SIGN IN CIGARETTE ADVERTISEMENTS - Ni Ketut Tila Ningsih; Ida Ayu Putri Gita Ardiantari (Jurnal CULTURE (Culture, Language, and Literature Review), 2022)
Abstract This study entitled “The Meaning Of Verbal And Non Verbal Sign In Cigarette Advertisements". Advertisements usually contains signs both verbal and non-verbal signs. This study found there are signs contained in advertisement of verbal and non-verbal signs. These advertisements are depicted from the words, pictures and utterances that appear. By using theory purposed by Saussure (1983) and by using Roland Barthes theory (1967), in this study to discuss and analyzes verbal and non-verbal visual sign in cigarette advertisements. The data source of this study is the cigarette advertisements of Esse, Marlboro, Surya, LA Bold, Camel, GG Mild, Gudang Garam Signature, and Lucky Strike. This study used observation method to collect the data that both verbal and non-verbal sign cigarette advertisements contain hidden message. Keywords: advertisement, verbal, non-verbal, sign, cigarette